2018
DOI: 10.1177/2050313x18775587
|View full text |Cite
|
Sign up to set email alerts
|

A silent massive ossification of Achilles tendon as a suspected rare late effect of surgery for club foot

Abstract: We report the case of a 66-year-old male patient with massive ossification of the distal portion of the Achilles tendon, as a late consequence of a surgical release for club foot conducted in his childhood. The singularity of the case report derives from its clinical features: the bone mass was of abnormal dimensions, almost substituting the entire tendon; the condition had always been asymptomatic, without deficits in range of motion, in absence of either pain or biomechanical defects with age. In fact, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Brotherton et al and Mallinson et al describe a technique wherein the ends of a fractured tendon can be brought and held together with a wire [18,19]. However, more commonly, the ossified segments of the Achilles are removed, with the remaining tendon ends reconnected with a tendon graft [4,5,10,[13][14][15]. Tendons from the flexor hallucis longus, hamstring, semitendinosus, gracilis, fascia lata, plantaris, and fascia overlying gastrocnemius-soleus muscle have all reportedly been used as tendon autografts [5,12,13,15] with no allografts or xenografts being used in the reports.…”
Section: Oliva Et Al 2012 [3]mentioning
confidence: 99%
“…Brotherton et al and Mallinson et al describe a technique wherein the ends of a fractured tendon can be brought and held together with a wire [18,19]. However, more commonly, the ossified segments of the Achilles are removed, with the remaining tendon ends reconnected with a tendon graft [4,5,10,[13][14][15]. Tendons from the flexor hallucis longus, hamstring, semitendinosus, gracilis, fascia lata, plantaris, and fascia overlying gastrocnemius-soleus muscle have all reportedly been used as tendon autografts [5,12,13,15] with no allografts or xenografts being used in the reports.…”
Section: Oliva Et Al 2012 [3]mentioning
confidence: 99%
“…Numerous cases of Achilles ossification describe previous corrective surgery for tallipes equinovarus, which is a common indication for Achilles tenotomy 13–16…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, intraoperative findings included a significant amount of scar tissue at the distal end of the tendon. Moreover, Pedrotti et al 17 and Manfreda et al 18 reported calcification and rupture of the Achilles tendon in adults with a history of treatment for clubfoot. Although these cases differed from the present case in that they had previously undergone more invasive surgery, we believe that the pathophysiology of calcification and rupture because of degeneration of the Achilles tendon is similar to that of the present case.…”
Section: Discussionmentioning
confidence: 99%